Efektifitas Metode Bernyanyi Terhadap Pengenalan Angka Anak di Taman Kanak-Kanak Aisyiyah Sumanik Kabupaten Tanah Datar - Rani Wulandari; Yulsyofriend Yulsyofriend (Dinasti Research, 2023)
This research is based on the background, namely the lack of various methods used in number recognition to develop children's knowledge about the shape of numbers. This can be seen when children are able to count but do not know the shape of numbers, the media used in number recognition is less attractive to children. This research was conducted with the aim of seeing the effectiveness of the singing method in the process of recognizing children's numbers in Aisyiyah Sumanik Kindergarten (TK) Tanah Datar District. The population of this study is 32 children at Kindergarten Aisyiyah Sumanik, Tanah Datar Regency. The technique for determining the sample is Cluster Sampling, which is a sampling technique when all members of the population are used as a sample, namely class B1 becomes the control group with a large number of 10 children and class B2 becomes a group for experiments with a large number of 10 children. Data collection techniques used tests, in the form of 8 item statements and techniques for analyzing data using normality testing, homogeneity testing and hypothesis testing with the help of the SPSS For Windows 15.0 application. If one pays attention to the research, it can be seen where the variance of the N-gain data is in the group for the experiment using the storytelling method and in the control group using the singing method, namely normal and homogeneous. Furthermore, if we pay attention to the table of results from the study, we can find out which score is sig (2-tailed) through a large score of 0.000 <0.05. So it can be concluded that the effectiveness of the singing method will recognize the number of children in Aisyiyah Sumanik Kindergarten, Tanah Datar Regency